Designing an Eco-Literate ESP Syllabus: Integrating Sustainability and Environmental Awareness into English for Fisheries Students - Isnawati, Uzlifatul Masruroh; Rohmah, Galuh Nur; Kholis, Adhan (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3802, 2025)
This study proposes an eco-literate ESP syllabus tailored for Fisheries Department students by integrating sustainability principles and environmental awareness into English instruction. Using the ESP course design model of Dudley-Evans and St. John (1998), the paper outlines a systematic process involving needs analysis, syllabus planning, material adaptation, and evaluation. The needs analysis highlights learners’ communicative demands in sustainability-focused contexts such as marine conservation, sustainable aquaculture, and the blue economy. The syllabus adopts content-based and task-based approaches, utilizing authentic environmental materials (e.g., research articles, policy documents, sustainability reports). Each unit centers on eco-related discourse, marine ecology vocabulary, and critical reflection on environmental ethics across reading, writing, and speaking tasks. Existing studies seldom address how environmental ethics, marine-related sustainability content, and SDG-oriented competencies can be systematically embedded into ESP courses targeting discipline-specific communication needs. This study fills that gap by proposing a structured eco-literate ESP syllabus that connects language learning with environmental responsibility in the fisheries context.